Answer:
The value of x is 2
Explanation:
* Lets explain how to find a distance between 2 points
- If the endpoints of a segment are
and
is
![d=\sqrt{(x_(2)-x_(1))^(2)+(y_(2)-y_(1))^(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ujhtkf4aepvi1g2p9lnhwfcocp96l102i2.png)
- Triangle ABC has a perimeter of 12 units
∵ The perimeter of any triangle is the sum of lengths of its sides
∴ P Δ ABC = AB + BC + AC
* Lets find the length of the three sides
∵ A = (x , 2) , B = (2 , -2) , C = (-1 , 2)
∵
![AB=\sqrt{(2-x)^(2)+(-2-2)^(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/nm3q2157eyxqdvjws1nin94kk1d7ai958s.png)
∴
![AB=\sqrt{(2-x)^(2)+(-4)^(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/w3yuusqo30vg4metj89yl72bwbbzv8di2v.png)
∴
![AB=\sqrt{(2-x)^(2)+16}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ar0f6cwiykzavrfhfngyn7y80q07ixviu1.png)
∵
![BC=\sqrt{(-1-2)^(2)+(2--2)^(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/xez2ig6zmoypgppah1u57f3usd76uqcsc5.png)
∴
![BC=\sqrt{(-3)^(2)+(4)^(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/wh0iqahbg8d3skiao2t6nuukphhyg22tt1.png)
∴
![BC=√(9+16)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/dfwvuvp476d8z4a4nqbwix9jm42zxatbrr.png)
∴
![BC=√(25)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/hpn2dloodlv5pu31wongp0aoyyhjtcrjeh.png)
∴ BC = 5
∵
![CA=\sqrt{(x--1)^(2)+(2-2)^(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/4596tzjso5w131ocpe1zrxdkw78aiie5cz.png)
∴
![CA=\sqrt{(x+1)^(2)+(0)^(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/tj0egni69s60u6b4lkhha6u4vuglb05lhe.png)
∴
![CA=\sqrt{(x+1)^(2)}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/oxmec3iuf82ibg91winycb185o06880rsl.png)
- The √ is canceled by power 2
∴ CA = (x + 1)
∵ AB + BC + CA = 12
∴
+ 5 + (x + 1) = 12
- Add 5 and 1
∴
+ 6 + x = 12
- subtract 6 and x from both sides
∴
= (6 - x)
- To cancel (√ ) square the two sides
∴ (2 - x)² + 16 = (6 - x)²
- Simplify the two sides
∴ [(2)(2) + (2)(2)(-x) + (-x)(-x)] + 16 = (6)(6) + (2)(6)(-x) + (-x)(-x)
∴ 4 - 4x + x² + 16 = 36 - 12x + x²
- Subtract x² from both sides
∴ 20 - 4x = 36 - 12x
- Add 12x to both sides and subtract 20 from both sides
∴ 12x - 4x = 36 - 20
∴ 8x = 16
- Divide both sides by 8
∴ x = 2
* The value of x is 2